Asthma in Children and Adults: A Shared Biological and Molecular Basis - Paolo M Renzi (Canadian Respiratory Journal)
The objective of this paper is to describe the important clinical, physiological, immunological and biological similarities among asthmatic infants, children and adults. A comparison of the reported clinical presentation, physiological changes, histology and cellular biology of asthma in different age groups is presented with special emphasis on the abnormal immune response, cellular activation and lymphokine production. Different age groups of asthmatics have important similarities in clinical presentation, lung physiology and histopathology. Eosinophilia and increased immunoglobulin (Ig) E levels are present at every age except in young infants. Signs of cellular activation and increased production of lymphokines of the type 2 helper T lymphocyte, which can increase IgE levels and affect eosinophils, are also found in every age group. These abnormalities have been shown in animal models to cause airway inflammation and physiological changes comparable with those encountered in asthma. In conclusion, future studies should try to identify the specific characteristics of the population at risk for asthma, emphasizing not only primary prevention but also the use of inhibitors or modulators of the inflammatory reaction that is present in the airways or asthmatics.